2005
DOI: 10.1074/jbc.m507941200
|View full text |Cite
|
Sign up to set email alerts
|

GSK-3β Directly Phosphorylates and Activates MARK2/PAR-1

Abstract: In Alzheimer disease (AD), the microtubule-associated protein tau is found hyperphosphorylated in paired helical filaments. Among many phosphorylated sites in tau, Ser-262 is the major site for abnormal phosphorylation of tau in AD brain. The kinase known to phosphorylate this particular site is MARK2, whose activation mechanism is yet to be studied. Our first finding that treatment of cells with LiCl, a selective inhibitor of another major tau kinase, glycogen synthase kinase-3␤ (GSK-3␤), inhibits phosphoryla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(37 citation statements)
references
References 47 publications
1
36
0
Order By: Relevance
“…Glycogen synthase kinase 3 (GSK3) (Frame and Cohen, 2001), was recently suggested to phosphorylate MARK2, potentially at a T-loop residue (S312) located four residues C-terminal to the threonine phosphorylated by LKB1 (Kosuga et al, 2005). It would be interesting to investigate whether proline-directed kinases and GSK3 could phosphorylate MARK2 at sites other than S312, and whether these phosphorylations can be modulated by inhibitors and/or extracellular stimuli that affect proline-directed kinase/GSK3 activity.…”
Section: Discussionmentioning
confidence: 99%
“…Glycogen synthase kinase 3 (GSK3) (Frame and Cohen, 2001), was recently suggested to phosphorylate MARK2, potentially at a T-loop residue (S312) located four residues C-terminal to the threonine phosphorylated by LKB1 (Kosuga et al, 2005). It would be interesting to investigate whether proline-directed kinases and GSK3 could phosphorylate MARK2 at sites other than S312, and whether these phosphorylations can be modulated by inhibitors and/or extracellular stimuli that affect proline-directed kinase/GSK3 activity.…”
Section: Discussionmentioning
confidence: 99%
“…It seems likely that several pathways converge to activate MARK2. For example, MARK kinase, LKB1 kinase, Pim-1, and GSK-3 can all phosphorylate MARK2 within its kinase domain (Timm et al, 2003;Bachmann et al, 2004;Lizcano et al, 2004;Kosuga et al, 2005), suggesting that multiple kinases, which may be differentially expressed in N2a cells and hippocampal neurons, potentially converge on MARK2 to regulate its activity. Similarly, downstream effectors of CaMKI may differ between neuronal types.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with previous findings that the EPIYA repeated region is responsible for the activation of b-catenin 45 , we found that a C-terminal region having an EPIYIA and multimerization domain plays an important role in binding to and depletion of GSK-3. Intriguingly, GSK-3 can phosphorylate PAR1/MARK2, which is responsible for tau phosphorylation in Alzheimer disease 46 .…”
Section: Discussionmentioning
confidence: 99%